Hubungan Antara Matrix Metalloproteinase-9 (MMP-9) Dengan Komplikasi Gagal Jantung Akut Pada Infark Miokard Dengan ST-Elevasi (STEMI) Dan Sindroma Koroner Akut Tanpa ST-Elevasi (NSTEACS) - Budi Yuli Setianto; Sofia Mubarika; Indwiani Astuti; Bambang Irawan (The Indonesian Heart Association, 2011)
Background. Acute coronary syndrome (ACS) often leads to complications of acute heart failure. These complications will increase the morbidity and mortality of patients with ACS.Objective. To determine differences in levels of MMP-9 between STEMI and NSTEACS and the correlation between MMP-9 with acute heart failure between the two groups.Methods. Examination of the samples performed in 79 patients with ACS (38 STEMI and 41 NSTEACS) prior to the action of intravenous thrombolytic or coronary intervention. Differences in levels of MMP-9 in the ACS are experiencing acute heart failure and without heart failure, and differences in levels of MMP-9 in the STEMI and NSTEACS groups were tested with Chi-square, Fisher’s exact test or the Independent t-test.Results. STEMI groups had significantly higher levels of MMP-9 than NSTEACS group 1629.12 ± 719.60 compared to 1033.42 ± 777.12 (p = 0.001). However, STEMI groups who have acuteheart failure are higher but not significant compared with NSTEACS group 14 (36.84) and 11 (26.82) (p = 0.339). There are differences in levels of MMP-9 in ACS with acute heart failure than those who did not: 1698 ± 867.95 ng/mL and 1144.61 ± 713.60 ng/mL (p = 0.004). Background. Acute coronary syndrome (ACS) often leads to complications of acute heart failure. These complications will increase the morbidity and mortality of patients with ACS.Objective. To determine differences in levels of MMP-9 between STEMI and NSTEACS and the correlation between MMP-9 with acute heart failure between the two groups.Methods. Examination of the samples performed in 79 patients with ACS (38 STEMI and 41 NSTEACS) prior to the action of intravenous thrombolytic or coronary intervention. Differences in levels of MMP-9 in the ACS are experiencing acute heart failure and without heart failure, and differences in levels of MMP-9 in the STEMI and NSTEACS groups were tested with Chi-square, Fisher’s exact test or the Independent t-test.Results. STEMI groups had significantly higher levels of MMP-9 than NSTEACS group 1629.12 ± 719.60 compared to 1033.42 ± 777.12 (p = 0.001). However, STEMI groups who have acuteheart failure are higher but not significant compared with NSTEACS group 14 (36.84) and 11 (26.82) (p = 0.339). There are differences in levels of MMP-9 in ACS with acute heart failure than those who did not: 1698 ± 867.95 ng/mL and 1144.61 ± 713.60 ng/mL (p = 0.004). Conclusion. MMP-9 levels are significantly higher in STEMI groups compared with NSTEACS groups, and MMP-9 associated with the incidence ofacute heart failure in ACS. STEMI groups have tended to have acute heart failure are higher than NSTEACS groups. MMP-9 levels are significantly higher in STEMI groups compared with NSTEACS groups, and MMP-9 associated with the incidence ofacute heart failure in ACS. STEMI groups have tended to have acute heart failure are higher than NSTEACS groups.